The search for the North West Passage - Savours, Ann. (New York : St. Martin's Press, 1999)
"The quest for a North West Passage through the Arctic seas to China and the riches of the Orient began as long ago as the sixteenth century when northern Europeans found the southern route around the Cape of Good Hope barred by the Spanish and Portuguese. It took a further 300 years, as well as the extraordinary bravery and resilience of the explorers, for this elusive route to be finally discovered by Franklin during his famous but ill-fated voyage in the 1840s. Not until the twentieth century was the passage finally traversed by ship."--BOOK JACKET.
"The expeditions which headed north into the unknown wastes of the Arctic did so in defiance of terrible odds, and the names of those who led them - Frobisher, Cook, Hudson, Davis, Baffin, Parry, Ross and Franklin himself - are central to the mythology of European exploration. This new book tells the story of their remarkable feats and describes how the vast tracts of the ice-bound archipelago were slowly and painfully charted. It portrays the encounters with the Esquimaux and examines their vital help; it describes the boats and ships and the food and clothing on which the explorers depended as well as the alien habitat in which they found themselves."--BOOK JACKET.
1. The Elizabethan Voyages -- 2. Henry Hudson and William Baffin -- 3. The Hudson's Bay Company, James Cook and the Eighteenth Century -- 4. Sir John Barrow and the Revival of Arctic Exploration in 1818 -- 5. The First Expeditions of Parry and Franklin -- 6. Franklin's Second Journey to the Polar Sea 1825-1827 -- 7. The Seaborne Voyages of Parry, Beechey and Lyon -- 8. John and James Clark Ross: Four Winters in the Arctic 1829-33 -- 9. Dease and Simpson along the North Coast of America 1836-39 -- 10. Sir John Franklin's Last Expedition 1845-48 -- 11. The Franklin Search Begins -- 12. The Search for Franklin from the Pacific -- 13. The Expeditions of Kennedy, Belcher, Inglefield and Kane 1851-1854 -- 14. The Discovery of the First Relics 1853-1855 -- 15. McClintock's Successful Search 1857-59 -- 16. The Last Searches -- 17. The Navigation of the North West Passage.
Includes bibliographical references and index.
Keywords: Northwest Passage